Clonal variability and divergence studies in Tamarindus indica L. - Divakara, B.N.; Ratha Krishnan, P.; Reddy, S. R. (Indian Journal of Agroforestry, 2020)
Exploration of clonal variability and divergence among thirty-five high fruit/pod yielding genotypes of Tamarindus indica L. selected from south India was carried out for further genetic improvement. Significant variation was expressed for all the growth characters under field condition. Maximum plant height (60.33 cm), number of branches (19.78) collar diameter (1.49 cm), and Volume index (245.78 cm3) was recorded by CPT-22, CPT-5 and CPT-7, respectively. Higher GCV (42.83%), heritability (78.98%) and genetic gain (78.40%) were found for volume index. All the morphometric traits registered positive and highly significant association with volume index at both phenotypic and genotypic level. Path analysis revealed that, collar diameter (0.594) followed by height (0.450) expressed maximum direct positive effect on volume index and number of branches contributed indirectly through height and collar diameter. Volume index contributed maximum for genetic diversity as per cent contribution and rank total, 34.96 and 208 respectively. Genetic diversity analysis resolved thirty-five genotypes under investigation into 6 clusters, indicating wide diversity. Cluster I contained eight genotypes and showed maximum intra cluster distance (2.74) closely followed by cluster-VI (2.73) because the genotypes used for breeding program were from different locations. The highest inter-cluster distance was found between cluster III and V (7.63) followed by II and V (7.45) suggesting wide diversity between these groups. Cluster V recorded maximum mean values for all traits; hence these genotypes can be directly selected and utilized for further improvement programme.